DAKWAH DAN KONDISI UMAT ISLAM DI ERA KONTEMPORER - Hasibuan, Sulham Efendi; Riskia, Ayu; Sopiah, Sopiah (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
This study examines the relationship between da’wah and the condition of the Muslim community in the contemporary era, which is characterized by social change, advances in digital technology, and shifts in societal patterns of thought. The development of digital media has transformed da’wah from conventional methods into more open and flexible forms that extend into virtual spaces such as social media and online platforms. This research employs a descriptive qualitative approach through literature review and observation of emerging digital da’wah phenomena in society. The findings indicate that da’wah and the development of the Muslim community have a reciprocal relationship that mutually influences one another. Modern challenges, including information overload, changing lifestyles, and identity crises, require da’wah to be adaptive, dialogical, and contextual. At the same time, innovations in digital da’wah shape patterns of religious practice, particularly among younger generations. This study affirms that da’wah functions not only as a means of conveying Islamic teachings but also as a medium for fostering social awareness, strengthening Islamic identity, and providing moral guidance for Muslims amid global dynamics. ABSTRAK Penelitian ini membahas keterkaitan antara dakwah dan kondisi umat Islam di era kontemporer yang ditandai oleh perubahan sosial, kemajuan teknologi digital, serta pergeseran pola pikir masyarakat. Perkembangan media digital telah mengubah wajah dakwah dari metode konvensional menjadi lebih terbuka, fleksibel, dan menjangkau ruang virtual seperti media sosial dan platform daring. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui studi pustaka dan pengamatan terhadap fenomena dakwah digital yang berkembang di masyarakat. Hasil kajian menunjukkan bahwa dakwah dan perkembangan umat Islam memiliki hubungan timbal balik yang saling memengaruhi. Tantangan modern, seperti banjir informasi, perubahan gaya hidup, dan krisis identitas, menuntut dakwah yang adaptif, dialogis, dan kontekstual. Di sisi lain, inovasi dakwah di ruang digital turut membentuk pola keberagamaan umat, khususnya generasi muda. Penelitian ini menegaskan bahwa dakwah tidak hanya berfungsi sebagai sarana penyampaian ajaran Islam, tetapi juga sebagai media pembinaan kesadaran sosial, penguatan identitas keislaman, dan penuntun moral umat di tengah dinamika global.